Effect of moisture, protein, starch, soluble sugar contents and microstructure on mechanical properties of maize kernels. (15th June 2022) - Qiao, Mengmeng; Xia, Guoyi; Cui, Tao; Xu, Yang; Gao, Xiaojun; Su, Yuan; Li, Yibo; Fan, Hongfei
Highlights: The relationships between components contents and mechanical properties of maize kernels were comprehensively studied. The prediction models of mechanical properties based on multi-indexes of components contents were built. The influences of the components contents on mechanical properties were explained through microstructure observation. A new method for accessing the mechanical properties of maize kernels was provided. Abstract: The relationships between components contents and mechanical properties of maize kernels were studied. The relationships were analyzed by gray relation analysis (GRA), correlation analysis (CA), and multiple linear regression (MLR). Furthermore, Scanning Electron Microscope (SEM) was utilized for interpreting mechanical properties. The results of GRA and CA indicated that soluble sugar content was not an important factor that can affect mechanical properties compared with the moisture, starch and protein contents. The results of MLR indicated that the regression models can be used to access the hardness, rupture force and apparent elastic modulus (R greater than 0.75), but cannot be used to access rupture energy and viscoelastic parameters. The microstructure observation illustrated that high protein content could increase hardness, rupture force, rupture energy, and elastic properties, while high starch content could increase viscous properties. This study can provide technical references for transportation, processing and harvest processes.